Leaf Epidermal Studies of two Species of Syzygium in Jos Plateau State Nigeria. - J.J. Azila,; J.J., Mbah; Shoyemi-Obawanle, A.O.; Olubunmi., Shoyemi Aduratola; S., Akintunde; S., Mafolasire; D.D., Jeridas (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2021)
The foliar epidermal and stomata study of the Syzygium species in Jos Plateau State Nigeria was carried out using standard anatomical procedure. The genus belong to family Myrtaceae and has two species in it which are present in the region. They include: Syzygium guineense var.guineense and Syzygium guineense var.macrocarpum.The study showed that epidermal cell shape,stomata type and stomata shape on both the adaxial and abaxial surfaces of the two plants were almost similar with little variation. Other systematically useful characters are stomata index,guard cell area and the shape of the anticlinal cell walls can also be used for distinguishing the species.